Institutional Profile: Cleveland Clinic's Center for Personalized Healthcare: setting the stage for value-based care. (April 2014) - Teng, Kathryn; DiPiero, Jennifer; Meese, Thad; Doerr, Megan; Leonard, Mandy; Daly, Thomas; Lacbawan, Felicitas; Chalmers, Jeff; Stowe, David; Knoer, Scott; Hicks, J Kevin
Cleveland Clinic (OH, USA) launched the Center for Personalized Healthcare in 2011 to establish an evidence-based system for individualizing care by incorporating unique patient characteristics, including but not limited to genetic and family health history information, into the standard medical decision-making process. Using MyFamily, a web-based tool integrated into our electronic health record, a patient's family health history is used as a surrogate for genetic, environmental and behavioral risks to identify those with an elevated probability of developing disease. Complementing MyFamily, the Personalized Medication Program was created for the purpose of identifying gene–drug pairs for integration into clinical practice and developing the implementation tools needed to incorporate pharmacogenomics into the clinical workflow. We have successfully implemented the gene–drug pairs HLA-B*57:01 –abacavir and TPMT –thiopurines into patient care. Our efforts to establish personalized medical care at Cleveland Clinic may serve as a model for large-scale integration of personalized healthcare.